2002
DOI: 10.1142/s1609945102000242
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Business Cycles for the Swedish Economy

Abstract: This paper consists of two parts. In the first part we carry out a traditional growth accounting exercise for the private business sectors of the Swedish economy. We search for structural breaks during the sample period, using Chow tests, using a dynamic specification of Total Factor Productivity (TFP) growth rates. Grangercausality tests are carried out for the nine sub-sectors of the private business sectors of the Swedish economy. We combine the growth rates of value added and hours worked and calculate lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…With both strong bull and bear markets, and calm and volatile periods in the sample, we suspect at least one structural break. To detect structural breaks, we use the recursive Chow tests (Barot, ). Ten variables are considered for the test: Daily return volatility and trading volume from the three markets, and daily open interests and log basis volatility from the two derivative markets.…”
Section: Datamentioning
confidence: 99%
“…With both strong bull and bear markets, and calm and volatile periods in the sample, we suspect at least one structural break. To detect structural breaks, we use the recursive Chow tests (Barot, ). Ten variables are considered for the test: Daily return volatility and trading volume from the three markets, and daily open interests and log basis volatility from the two derivative markets.…”
Section: Datamentioning
confidence: 99%
“…The Chow test is widely used to examine whether a structural break exists in a time series. To apply this test, we rely on a recursive scheme following Barot (2002) and Ahn et al (2019). Five variables are used for this structural break search: daily spot trading volume, daily options trading volume, daily spot return volatility, daily options return volatility, and daily basis volatility.…”
Section: Resultsmentioning
confidence: 99%
“…Anaman (2003) investigated the relationship between the GDP contributions of the construction industry and overall GDP in Brunei using Granger causality tests. Barot (2002) used Granger causality tests to study whether growth rate in investment impacted growth rates in total factor productivity for agriculture and financial institutions, real estate, and other businesses. Ofori (1988) studied the impact of construction in Singapore's economy and concluded that the construction sector played a major role in Singapore's economic development.…”
Section: Introductionmentioning
confidence: 99%